If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2z + 1) + -9 = 13 Reorder the terms: 2(1 + 2z) + -9 = 13 (1 * 2 + 2z * 2) + -9 = 13 (2 + 4z) + -9 = 13 Reorder the terms: 2 + -9 + 4z = 13 Combine like terms: 2 + -9 = -7 -7 + 4z = 13 Solving -7 + 4z = 13 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 4z = 13 + 7 Combine like terms: -7 + 7 = 0 0 + 4z = 13 + 7 4z = 13 + 7 Combine like terms: 13 + 7 = 20 4z = 20 Divide each side by '4'. z = 5 Simplifying z = 5
| 216-2x=x^2+8x+16 | | 40=2(3w+4)+2w | | 5(e+6)=(4e+7) | | 3+3=d | | -7v=49 | | 2n=4n+4 | | y=(0)2-3 | | v^3-2v^2-16v=-32 | | 3(x^2-2x)=0 | | 9(x-6)=7x+60 | | v^3-2v^2-16=-32 | | 21-a=-8 | | 82+(3x+2)=180 | | 23+8x=-3(1-7x) | | (4x-1)(4x-1)+9=0 | | 4(x+5)=4(x+10) | | m-12=7m-6 | | 7(3s-5)=49 | | 0=x^2+x-9 | | 26+6x=9x | | 8(x-4)=2(x+6) | | y=(x+9)+12 | | (2/3)x-11=x+4 | | 11g+34=9g | | y=10.25x+1.25x | | 2(5v-2v)=(v-5) | | -3x=-34+4y | | 8(x-5)=-3(x-17) | | 8x+11=-9x-16 | | 4x=x+8+3x | | 7x-11=-46 | | a^3-4a^2+4a=0 |